Abstract ID: 201 Code sharing of MC beam models for advanced radiotherapy. (October 2017) - Price, Tony; Gutierrez, Andrea; Panaino, Costanza; Turner, Martin; Owen, Hywel
Abstract : The development and validation of a beam line MC model is an essential part of many projects, particularly those involving particle therapy. This is often a very time consuming and sometimes costly computational process. However, many experiments use the same beam lines and the medical physics community would benefit greatly from a structured code and data sharing site. A new project[1], funded through the STFC Global Challenge Network+ in Advanced Radiotherapy[2], aims to collate, host, validate experimentally, and disseminate common Geant4 beam line models. We will present an overview of the aims of the project, and details of how to gain access to these structured models; a structured model includes both code and data with related information on use and best practice. To illustrate this, three validation results will be shown; the iThemba LABS proton therapy centre in Cape Town (South Africa), the medical beam line of the University of Birmingham MC40 Cyclotron (United Kingdom), and ongoing work with multiple models of the Clatterbridge Cancer Centre proton eye therapy beam line (United Kingdom). We aim to develop these models in TOPAS/GATE to facilitate their use for non Geant4/C++ experts, for example, medical physicists working in hospitals. A status report of this final step will be provided.